The Effect of Preeclampsia in Pregnant Women on The Incidence of Maternal Mortality: Literature Review - Oktaria, Riski Resa; Setriana, Tia; Merylista, Sofia; Fusfitasari, Yenni; Harison, Nunu (JURNAL INFO KESEHATAN, 2024)
Preeclampsia is a severe pregnancy complication characterized by elevated blood pressure and often occurs after 20 weeks of gestation. This condition can lead to significant morbidity and mortality for both the mother and the fetus. This study aims to identify the risk factors associated with preeclampsia in pregnant women, a condition that remains prevalent in Indonesia and globally. The research employed a comprehensive literature review method, examining ten articles sourced from databases such as Google Scholar, PubMed, and Elsevier. The inclusion criteria for the literature review involved studies focused on the causes and consequences of preeclampsia, published within the last ten years, and providing substantial data on maternal mortality. The results of the literature review indicated that pregnant women with a history of hypertension or previous preeclampsia are at a significantly higher risk of developing preeclampsia. Additionally, severe cases of preeclampsia, such as those involving HELLP syndrome, eclampsia, and high diastolic blood pressure, were strongly linked to increased maternal mortality. The review also highlighted the crucial role of efficient referral systems and timely medical interventions in managing severe preeclampsia and reducing maternal deaths. This study concludes that early detection and continuous monitoring are essential for managing preeclampsia effectively. The findings underscore the need for standardized treatment protocols, improved healthcare access, and comprehensive prenatal services to mitigate the risks associated with preeclampsia. Future research should aim to include a broader range of studies and explore the long-term implications of preeclampsia on maternal and fetal health. These insights are critical for developing effective strategies to reduce the incidence and severity of preeclampsia and enhance maternal health outcomes.